Surgical procedures for treatment of adult acquired flatfoot deformity: a network meta-analysis - Xu Tao; Wan Chen; Kanglai Tang (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Adult acquired flatfoot deformity (AAFD) represents a spectrum of deformities affecting the foot and the ankle. The optimal management of AAFD remains controversial. We evaluated the efficacy of surgical treatments of AAFD using both direct and indirect evidences. Methods We searched PubMed, EmBase, and the Cochrane Library to identify eligible studies conducted through November 2018. To compare different surgical strategies, we performed a network meta-analysis. A traditional meta-analysis using a random-effects model was used to evaluate the pooled outcome. Results A total of 21 studies including 498 patients were collected and analyzed. Network meta-analysis results based on lateral angle talocalcaneal-calcaneal pitch (LAT-CP) indicated that medial displacement calcaneal osteotomy (MDCO) has the highest probability to be the best course of AAFD treatment. However, analyses based on anteroposterior talo-first metatarsal (AP-TMT1) and lateral angle talocalcaneal talo-first metatarsal (LAT-TMT1) suggested that lateral column lengthening (LCL) was the best treatment, while those based on lateral angle talocalcaneal-arch height, anteroposterior talocalcaneal (AP-TC), lateral angle talocalcaneal-talocalcaneal (LAT-TC), anteroposterior-talonavicular coverage (AP-TNC), talonavicular coverage (TNC), and the American Orthopedic Foot and Ankle Society (AOFAS) indicated triple arthrodesis (TAO) as the best treatment. Moreover, double arthrodesis (DAO) provided the best treatment effect on the function score. Furthermore, according to traditional meta-analysis, the summary of standardized mean differences (SMD) indicated that the surgical interventions are associated with significant improvements in LAT-CP (SMD − 1.78), LAT-arch height (SMD − 4.95), AOFAS (SMD − 5.24), AP-TMT1 (SMD 2.45), LAT-TMT1 (SMD 1.97), AP-TC (SMD 3.05), LAT-TC (SMD 2.20), AP-TNC (SMD 2.07), TNC (SMD 1.70), and function score (SMD 0.95). Conclusions Our findings indicated that MDCO, LCL, TAO, or DAO might be the best surgical approaches for AAFD treatment. Furthermore, patients who received surgical interventions had significant improvements in symptoms and function.